2017
DOI: 10.1016/j.resp.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Breath-holding test in evaluation of peripheral chemoreflex sensitivity in healthy subjects

Abstract: A breath-holding test after deep inspiration reflects the sensitivity of the peripheral chemoreflex as defined by the single-breath carbon dioxide test in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 20 publications
2
31
0
1
Order By: Relevance
“…We note, however, that breath‐hold duration has previously been linked with elevated chemosensitivity during wakefulness (Stanley et al . ; Trembach & Zabolotskikh, ). In 1975, Stanley and coworkers (Stanley et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We note, however, that breath‐hold duration has previously been linked with elevated chemosensitivity during wakefulness (Stanley et al . ; Trembach & Zabolotskikh, ). In 1975, Stanley and coworkers (Stanley et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, the strong associations observed, by us and others (Stanley et al . ; Trembach & Zabolotskikh, ), indicate that variability in maximal breath‐hold duration generally reflects variability in loop gain more than it reflects variability in the “breaking‐point” (i.e. the change in chemical drive that triggers voluntary breath‐hold termination).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the duration of a voluntary breath-holding during a Breath-Holding Test (BHT) indirectly reflects the sensitivity of peripheral chemoreflex to carbon dioxide in subjects without cardiac and respiratory diseases [ 14 ]. However, its reproducibility and relationship with SB-CO 2 test was not evaluated in patients with HF previously.…”
Section: Introductionmentioning
confidence: 99%
“…Накануне операции в первой половине дня проводили определение чувствительности периферического хеморефлекса методом регистрации длительности произвольного порогового апноэ (ППА) [8]. В зависимости от длительности ППА пациенты обеих групп были разделены на подгруппы: пациенты с высокой чувствительностью периферического хеморефлекса -группа В (n=79); пациенты с оптимальной чувствительностью периферического хеморефлекса -группа Н (n=97).…”
Section: материалы и методыunclassified